Model studies of the role of oxygen in the FLASH effect. Issue 3 (18th August 2021) - Favaudon, Vincent; Labarbe, Rudi; Limoli, Charles L.
Abstract: Current radiotherapy facilities are standardized to deliver dose rates around 0.1–0.4 Gy/s in 2 Gy daily fractions, designed to deliver total accumulated doses to reach the tolerance limit of normal tissues undergoing irradiation. FLASH radiotherapy (FLASH‐RT), on the other hand, relies on facilities capable of delivering ultrahigh dose rates in large doses in a single microsecond pulse, or in a few pulses given over a very short time sequence. For example, most studies to date have implemented 4–6 MeV electrons with intra‐pulse dose rates in the range 10 6 –10 7 Gy/s. The proposed dependence of the FLASH effect on oxygen tension has stimulated several theoretical models based on three different hypotheses: (i) Radiation‐induced transient oxygen depletion; (ii) cell‐specific differences in the ability to detoxify and/or recover from injury caused by reactive oxygen species; (iii) self‐annihilation of radicals by bimolecular recombination. This article focuses on the observations supporting or refuting these models in the frame of the chemical‐biological bases of the impact of oxygen on the radiation response of cell free, in vitro and in vivo model systems.